REDESCRIPTION OF DACTYLOGYRUS KALYANENSIS, MUSSELIUS AND GUSSEV (1973) FROM GILLS OF WALLAGO ATTU AT GHAZIABAD.: Life Sciences-Zoology - PRAGATI RASTOGI; KAVITA RANI; DEEPMALA MISHRA; JYOTI SINGH (International Journal of Life Science and Pharma Research, 2022)
Present communication deals with a known species of genus Dactylogyrus Diesing, 1850 from freshwater fish Wallago attu (Bloch and Schn). Generic diagnosis of genus Dactylogyrus is as follows: Cephalic lobes two pairs. Eye spots two pairs, may disintegrate into eyespot granules or entirely absent in adult. Anchors directed by their points to dorsal side, supported by 1-3 connective bars. Vas deferens usually loops around left intestinal limb. Seminal vesicle formed by mere dilation of vas deferens. Two prostatic reservoirs present. Copulatory organ mostly tubular, with accessory piece. Vagina single, exceptionally double, may or may not have sclerotised supporting structures, opens near right (rarely near the left) side of the body. Parasites of freshwater teleosts. D. kalyanensis has been collected and described in India from gills of Catla catla (a Cyprinid fish) by Musselius and Gussev (1973) and Kumar (2013) from Kalyani fishfarms in West Bengal and Sharanpur in Uttar Pradesh respectively. D. kalyanensis has been collected from a new host Wallago attu (Bloch and Schn) (a Silurid fish) for the first time at a new locality in India.. The initial account given by Musselius and Gussev (1973) lacks the details of soft anatomy and male gonopore. However, the more recent account given by Kumar (2013) shows some discrepancies with regards to the description of structure of parasite. Therefore, D. kalyanensis Musselius and Gussev (1973) is redescribed from the gills of Wallago attu at Ghaziabad based on fresh material collected by authors. D. kalyanensis is characterized by the shape of its accessory piece and cirrus, together with its vaginal armament and egg